The Beneficial Effect of Combining Feedback, Observational Learning and Motor Imagery on Football Pass Performance - Nicolas Robin; Eric Joblet; Emmanuel Roublot; Guillaume R. Coudevylle (Desafio Singular, 2020)
The aim of this original research was to investigate the effect of a combination of feedback, action observation of a model and motor imagery on passes accuracy in non-expert football players. All the participants performed a pre-test, 5 week-intervention sessions, and a post-test similar to the pre-test. The task consisted in passing toward a target located at 20-meters in an outdoor football field. During each session, the participants, divided in Control (i.e., physical practice only), Feedback, Model, Imagery and Feedback plus Model plus Imagery (FMI) groups performed 3 blocks of 4 trials. After each block, they received or not a feedback by the coach, watched a clip or a video of a peer skilled model touching the target, and finally realized a mental task or motor imagery. The main results of this study revealed that the FMI group increased the performance from the pre- to the post-test whereas the performance of all the other groups remained stable across the experimental conditions. The current study showed the beneficial effect of combining the observation of a model, the motor imagery and expert feedback after physical practice especially in case of short learning session in non-expert football players.